GAMBARAN TINGKAT PENGETAHUAN IBU NIFAS TENTANG TANDA- TANDA BAHAYA SELAMA MASA NIFAS DI KLINIK MARIANA SUKADONO TAHUN 2019 - Ermawaty Arisandi Siallagan; Merlina Sinabariba; Sri Handayani Hia (Elisabeth Health Jurnal, 2020)
Introduction: In Indonesia, in one hour, two mothers die from complications of pregnancy, childbirth and childbirth. Postpartum care is needed during this period because it is a critical period for both mother and baby. With close monitoring and care for mothers and babies during the postpartum period, it can prevent several deaths. This research aims to describe the knowledge of postpartum mothers about the danger signs during childbirth at the Mariana Sukadono clinic in 2019.Method: The method used in the study was a descriptive design and the sample in this study was 30 postpartum mothers who gave birth in this clinic with total sampling technique. The instrument used in this study was a questionnaire.Result: The results showed that the level of knowledge of mothers about danger signs during childbirth was more lacking (70.0%).Duscussion: Postpartum mothers are expected to know or seek information about danger signs during the puerperium during their spare time so that they are able to recognize danger signs during the postpartum period that might occur.